2009
DOI: 10.1124/mol.108.053793
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Potassium Stabilizes HumanEther-à-go-go-Related Gene Channels for Export from Endoplasmic Reticulum

Abstract: Several therapeutic compounds have been identified that prolong the QT interval on the electrocardiogram and cause torsade de pointes arrhythmias not by direct block of the cardiac potassium channel human ether-à -go-go-related gene (hERG) but via disruption of hERG trafficking to the cell surface membrane. One example of a clinically important compound class that potently inhibits hERG trafficking are cardiac glycosides. We have shown previously that inhibition of hERG trafficking by cardiac glycosides is ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…Novel approaches include potassium supplementation for LQT2 patients. In vitro experiments have showed that proper intracellular K + concentration is a requirement for normal HERG channel trafficking to the membrane, and that extracellular potassium modulates HERG current (Guo et al, 2009;Wang et al, 2009). These findings correlate with earlier studies that focused on HERG current density, showing that I Kr current paradoxically increased when extracellular K + concentration was increased (Sanguinetti & Jurkiewicz, 1992).…”
Section: Therapeutic Approachessupporting
confidence: 80%
“…Novel approaches include potassium supplementation for LQT2 patients. In vitro experiments have showed that proper intracellular K + concentration is a requirement for normal HERG channel trafficking to the membrane, and that extracellular potassium modulates HERG current (Guo et al, 2009;Wang et al, 2009). These findings correlate with earlier studies that focused on HERG current density, showing that I Kr current paradoxically increased when extracellular K + concentration was increased (Sanguinetti & Jurkiewicz, 1992).…”
Section: Therapeutic Approachessupporting
confidence: 80%
“…Figure 6 shows a Western analysis of brefeldin A-treated hERG gradient fractions, illustrating the distribution of hERG in two prominent protein peaks, P1 and P2, with the majority of hERG protein present in P2. Using Blue Native-PAGE, we have previously determined that hERG is present as monomer or dimer in peak P1, whereas it forms channel tetramers in P2 (Wang et al, 2009). It is noteworthy that we could detect no quantitative differences in the distribution of hERG on sucrose gradients as a consequence of pentamidine exposure.…”
Section: Drug-induced Trafficking Inhibition 201mentioning
confidence: 45%
“…Soluble material (400-800 g of total protein) was layered onto 15 to 45% sucrose gradients (150 mM NaCl, 10 mM Tris, pH 7.4, and 0.1% digitonin). Gradients were made using BIOCOMP Gradient Mate (BIOCOMP, Fredericton, NB, Canada) as described previously (Wang et al, 2009). After centrifugation, 275-l fractions were collected manually from the top of each gradient.…”
Section: Drug-induced Trafficking Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some drugs disrupt HERG forward trafficking, thereby causing LQTS (13,33,34). Recently, Wang et al found that inhibition of Na + /K + ATPase disrupted HERG forward trafficking (34,35). However, the 0 mM K + -induced reduction of 155-kDa HERG expression levels is most likely due to the increased membrane instability and degradation of HERG channels, not to the impaired forward trafficking.…”
Section: Discussionmentioning
confidence: 95%